A Design And Build A Laundry Service Ordering Information System Using Framework Spring Boot And Vue Js (Case Study Qu Cuci Garut) - Elin Rosliani; Budiman, Tedi; Hidayat, Syarif (RISTEC : Research in Information Systems and Technology, 2023)
Currently, the development of Information Systems (IS) and Information Technology (IT) is progressing very quickly. The development of IS/IT cannot be separated from the role of humans who continue to improve and look for new innovations at all times so that technology can make people's daily work easier. The rapid development of IS/IT and the use of IS/IT in aspects of life has resulted in the integration of computerized systems that are not limited by time and distance via the network.internet. SI/IT also provides data accuracy in processing data compared to manual methods. The positive impact of IS/IT in the business world is not only felt by large-scale businesses but is also felt by medium and small businesses, where involving IS/IT in running their business will make business easier, faster and minimize human error.Main Quality (Qu Cuci) Garut is a service that operates in the service sectorlaundry kilos such as carpets, daily clothes and other types of fabric. However, Qu Cuci Garut in its operational process still uses manual and simple books, where the financial book process still uses manual stationery which is prone to damage to books, loss of books or writing that is difficult to read and for self-payment with current technological developments there are many payments. non-cash using the methodpayment gateway Therefore, an information system is needed to simplify the transaction process. Therefore, an information system is needed for online ordering and financial recording with a computerized system where payment methods are usedpayment gateway midtrans. Here the system that will be created usesFramework Spring Boot forBack End andFramework Vue Js forFront End.